The Methodology of the Prophet In Calling To Allah (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The Prophets call to Islam which started from his immediate family and relatives and then extended onto and went beyond the whole of Arabian Peninsula continued throughout his life with enormous achievement. The methods he implemented in his invitation to Islam were consistent, reasonable, systematic, and realistic and they yielded success. Following this path, the Prophet established around him a group of believers and then created the community who would spread his call onto other lands. He sent letters of invitation to the heads of neighboring states as the Messenger of Allah, and thus he began to spread his call at a universal level, which accelerated in an unprecedented fashion over the following centuries.